Rising to the challenges: Solution‐based case studies highlighting innovation and evolution in reformulation. Issue 3 (3rd September 2020) - Poole, J.; Bentley, J.; Barraud, L.; Samish, I.; Dalkas, G.; Matheson, A.; Clegg, P.; Euston, S.R.; Kauffman Johnson, J.; Haacke, C.; Westphal, L.; Molina Beato, L.; et al.
Abstract: Over the last few years, food research and development have increasingly focused on reformulation, balancing desired dietary changes with environmental considerations and consumer acceptability. This article includes a selection of case studies, from across food industry sectors, which have responded to health and sustainability trends and challenges with creative solutions. These include innovative ingredients that may facilitate sugars and saturated fat reduction and increase the amount of fibre and healthy fats in products. The case studies, written by company personnel and academic researchers, illustrate the breadth of food and nutrition‐related initiatives that are currently being undertaken to help develop potentially healthier, more nutritious or more environmentally responsible foods for the future, whilst at the same time helping to satisfy consumer demand for cleaner labels. They were selected by the British Nutrition Foundation (BNF) as useful examples of ongoing innovation in this field. BNF also invited Jon Poole from the Institute of Food Science and Technology to describe some of the key challenges for reformulation and new product development.